Cisplatin-, Doxorubicin-, and Docetaxel-Induced Cell Death Promoted by the Aqueous Extract of Solanum nigrum in Human Ovarian Carcinoma Cells. (November 2015) - Wang, Chia-Woei; Chen, Chun-Liang; Wang, Chien-Kai; Chang, Yu-Jia; Jian, Jiun-Yu; Lin, Chi-Shian; Tai, Cheng-Jeng; Tai, Chen-Jei
Chemotherapy is a major clinical treatment for managing patients with advanced and recurrent ovarian cancer. However, the clinical performance of chemotherapy is limited, and adverse effects have been observed. Integrating chemotherapy with current chemotherapeutic drugs and novel antitumor ingredients might improve the clinical performance of current chemotherapy for ovarian cancer. The aqueous extract of Solanum nigrum leaves (AE-SN), a key ingredient in many traditional Chinese medicine formulae, has exhibited tumor suppression efficacy in numerous human cancer cells but not in ovarian cancer cells. In this study, tumor suppression efficacy was determined using the ES-2, SKOV-3, and OVCAR-3 human ovarian cancer cell lines. The half-maximal inhibitory concentrations of the AE-SN in ES-2 and SKOV-3 cells were 1.052 and 1.779 mg/mL, respectively. AE-SN treatment increased the accumulation of mammalian microtubule-associated protein 1 light chain 3 A/B, an autophagic cell marker, in all the tested cell lines; however, it activated the cleavage of caspase-3, an apoptotic marker, only in SKOV-3 cells. Furthermore, the AE-SN also promoted tumor suppression efficiency of cisplatin, doxorubicin, and docetaxel in the tested ovarian cancer cells. In addition, AE-SN-enhanced cell death was associated with AE-SN-induced caspase-3 cleavage in SKOV-3 cells. In conclusion, the AE-SN exhibited tumor suppression efficacy and improved the tumor suppression efficiency of cisplatin, doxorubicin, and docetaxel in human ovarian cancer cells. Therefore, the AE-SN is a candidate antitumor ingredient that can be used in developing future integrated chemotherapy for managing ovarian cancer.